Is Entrepreneurial Orientation The Most Important Thing for The Performance of Micro, Small, and Medium Enterprises? - Fadillah, Haqi; Augustine, Yvonne (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study examines the impact of entrepreneurial orientation and Management Control System Packages (MCS Packages) on the performance of Micro, Small, and Medium Enterprises (MSMEs), with a competitive strategy scale as a moderating variable. This study used a mixed approach, which combines quantitative analysis through multiple regression and a qualitative approach through analysis of interview results. The study results indicate that entrepreneurial orientation and MCS packages positively affect MSME performance, with Entrepreneurial Orientation having a more significant influence than the MCS Package. This result confirms the importance of Entrepreneurial Orientation in improving MSME performance. The competitive strategy scale has also proven effective in moderating the influence of both variables. This study has practical implications in helping MSMEs enhance performance by implementing appropriate management control systems and entrepreneurial strategies. Socially, these results can guide stakeholders in designing policies that support the sustainability of MSMEs. The study’s originality lies in developing the entrepreneurial orientation variable by adding the entrepreneurial literacy dimension and the MSME performance variable by adding the business sustainability dimension. This research shows that MSME practices can support sustainability through resource optimization, environmentally friendly product innovation, and improving community welfare, contributing to economic competitiveness and sustainable development goals.